Design of an Employee Recruitment System Based on the AHP-MOORA Algorithm Case Study of PT XYZ - Ripin, Muhamad; Triayudi, Agung; Ningsih, Sari (Unversitas Muhammadiyah Riau, 2024)
The development of internet-based information technology has had a positive impact on human survival. One of the benefits of the Internet is support in building an employee recruitment system that is oriented towards good corporate governance. PT XYZ is a company that has been recruiting manually. Therefore, it is necessary to build an internet-based system for the employee recruitment process. This research uses the Analytical Hierarchy Process - Multi-Objective Optimization based on Ratio Analysis (AHP-MOORA) algorithm to determine the best applicants based on several criteria. The criteria used in this research are age, academic certificate, highest level of education, and work experience. The results of this study show that age and academic certification are priority criteria based on weight assessment using the AHP approach. Furthermore, five applicants became samples in application testing. The MOORA test results showed that three applicants had the highest scores. This research concludes that the application of the AHP-MOORA algorithm can provide objective results in determining applicants who meet the specified criteria.